2022
DOI: 10.7554/elife.81943
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively active STING causes neuroinflammation and degeneration of dopaminergic neurons in mice

Abstract: Stimulator of interferon genes (STING) is activated after detection of cytoplasmic dsDNA by cGAS (cyclic GMP-AMP synthase) as part of the innate immunity defence against viral pathogens. STING binds TANK-binding kinase 1 (TBK1). TBK1 mutations are associated with familial amyotrophic lateral sclerosis, and the STING pathway has been implicated in the pathogenesis of further neurodegenerative diseases. To test whether STING activation is sufficient to induce neurodegeneration, we analysed a mouse model that exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 85 publications
7
37
0
Order By: Relevance
“…Therefore, our results suggest that the observed neuroprotection of pharmacological blockade of STING in our study may be related with the inhibition of NLRP3 in ammasome-mediated signaling in addition to type I IFN-dependent pathways, although the mechanisms underlying the STING effect on NLRP3 activation are not clearly understood. The results of our work were consistent with a recent study showing that in ammasomes were activated and contributed to STING-mediated neuroin ammation in STINGN153S knock-in mice [10].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, our results suggest that the observed neuroprotection of pharmacological blockade of STING in our study may be related with the inhibition of NLRP3 in ammasome-mediated signaling in addition to type I IFN-dependent pathways, although the mechanisms underlying the STING effect on NLRP3 activation are not clearly understood. The results of our work were consistent with a recent study showing that in ammasomes were activated and contributed to STING-mediated neuroin ammation in STINGN153S knock-in mice [10].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, mice de cient for the PD-associated proteins PTEN-induced kinase 1 (PINK1) and parkin show a STING-mediated in ammatory phenotype after exhaustive exercise [12]. It is also worth noting that a relatively recent publication by Szego et al reported that STING activation was su cient to induce neurodegeneration by using a genetic mouse model that expresses the constitutively active STING variant N153S [10]. Together these ndings implicate the cGAS-STING pathway in driving the damaging in ammatory processes present in PD, making it an important therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies within the last 5 yr have associated STING signaling with a wide range of neurodegenerative diseases including amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), PD, as well as several monogenic diseases such as NGLY1 deficiency ( Yang et al, 2018 ) and NPC disease ( Chu et al, 2021 ). Additionally, recent work has demonstrated neuroinflammation and degeneration of dopaminergic neurons in a mouse model of chronic STING activation (SAVI, N153S; Szego et al, 2022 ). Both ligand-mediated (e.g., mitochondrial defect) and trafficking-mediated (e.g., endolysosomal defect) STING signaling mechanisms have been implicated in neurodegenerative diseases.…”
Section: Introduction and Evolution Of The Cyclic Gmp-amp Synthase–st...mentioning
confidence: 99%